A unified aging compact model for hot carrier degradation under mixed-mode and reverse E-B stress in complementary SiGe HBTs. (October 2020) - Mukherjee, C.; Fischer, G.G.; Marc, F.; Couret, M.; Zimmer, T.; Maneux, C.
Abstract: This paper presents an accurate, comprehensive and physics-based aging compact model for stress-induced degradation due to hot-carrier generation and oxide trapping in advanced complementary NPN and PNP SiGe HBTs. The analytical model equations are derived from the solution of reaction–diffusion theory and Fick's law of diffusion combined with oxide trapping mechanism under accelerated stress conditions. The model accuracy has been validated against results from long-term aging tests performed close to the safe-operating-areas of an advanced complementary 0.25 µm BiCMOS technology. Degradation asymmetry observed between NPN and PNP devices is accurately captured by this unified aging compact model. This study highlights the challenges of predicting degradation of complementary circuits and thereby improving its functionalities by designing better-matched NPN and PNP HBTs.